Generalized Multiprotocol Label Switching convergence NETWORKS IN THE SCHEME - Eriek Eriek Orlando (STMIK Jakarta, 2004)
Convergence of Internet and telecommunications, with applications in it are more and morebandwidth with QoS penqaturan it finally takes the network and the elements in it which gavefull support to the preservation and improvement of network performance. If the bandwidth isalways the first object is predicted, then the current scheme requires some applications have